IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH NU DAN MUHAMMADIYAH DALAM MEWUJUDKAN ISLAM WASHATIYYAH - Hayumi Hayumi (QATHRUNÂ, 2019)
The purpose of this research is to know the process of learning about Islamic Washatiyah in the process of NU and Muhammadiyah, and also to find out the obstacle and supporting factors in the learning processes. Based on topic, the researcher used a qualitative method, which is a field research to examine the condition of a natural object, which is something that is not manipulated circumstances and conditions. Qualitative research seeks to provide a systematic overview of stimuli and factual events on factors, traits, and relationships between the phenomena that they have to do the basics. This method is very relevant to the purpose or direction of research, understanding the situation of the research site and uncovers the natural condition, related to the study of Islamic religious education in realizing Islamic Islam. Data analysis is the process of recording, drafting, processing, and interpretation, as well as linking the meaning of data that has to do with the research problem, data reduction, data description, and data classification. The conclusion of the research process at the school Plus Malnu Pandeglang SMA and SMA Muhammadiyah City Serang until finishing of data collection will continue to be verified so that the conclusion is obtained a thorough, thus the conclusion in the study is expected to answer the formulation of problems that have been formulated from the beginning. Because NU and Muhammadiyah schools are the leading in preventing radicalism and intolerance for the realization of Islamic wasathiyah.